Manejo da ventilação em sistema compost barn: implicações na ambiência e bem-estar de vacas leiteiras - Danelus, Fernanda Lais (2020)
Given the limited scientific information on ventilation in compost barn systems and how this influences the thermal environment, welfare, thermoregulation and behaviour of dairy cows and the moisture content of the litter, this research aimed to evaluate whether different ventilation conditions in a compost barn confinement system affect bed quality, thermal comfort and behaviour of lactating cows. The research was carried out in the city of Campo Erê-SC, in a compost barn system with capacity for 72 animals, between December 2018 and January 2019. In total, 19 lactating Holstein animals were evaluated. As treatments, three ventilation programs were instituted with automatic activation by sensors, from determined temperatures. Program 1 consisted of activating the ventilation when the internal temperature of the barn exceeded 19ºC (P1), program 2, when it exceeded 22ºC (P2) and program 3, above 25ºC (P3). These treatments were randomly distributed and lasted for seven days. In each of these programs, the humidity and temperature of the bed (surface and interior), thermal variables of the internal and external environment (air temperature, air relative humidity and wind speed), temperature and humidity index, thermal comfort of the animals (hair coat surface temperature and respiratory rate), animal behaviour and welfare (hygiene and lameness score). As a result, we found that the ventilation programs did not affect the quality of the bed. P3 showed the lowest values of the surface temperature of the bed (below 25°C) at the hottest times of the day. Concerning the thermal environment of the barn, this same ventilation program provided lower values of wind speed (average of 3 m s-1). However, it presented better indexes of temperature and humidity - THI (average of 72,5). The animal behaviour was influenced by the ventilation programs and the thermal environment of the installation, with P3 being less likely to be in standing rest (probability of 0,5), walking (probability of 0,5) and drinking water (probability of 0,3) during the hot periods of the day (starting at 11:30 h). For thermoregulation and welfare, the animals' surface temperature (33°C) and hygiene score were better for P3 compared to other programs. In conclusion, the best activation temperature for the ventilation system is 25°C, as it offers better thermal comfort and animal welfare.